2021
DOI: 10.1021/acs.jchemed.1c00405
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Course-Level Social Belonging (Sense of Belonging and Belonging Uncertainty) and Academic Performance in General Chemistry 1

Abstract: Students' social belonging in a general chemistry course has been shown to predict academic performance in that course. Additionally, students' social belonging at the beginning of a general chemistry course has been shown to differ across demographics, such as gender. This social belonging exists as both an absolute sense of belonging in the course and as an uncertainty in that belonging. Both social-belonging components are important for students' performance and retention in science, technology, engineering… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 35 publications
(72 citation statements)
references
References 50 publications
4
63
1
Order By: Relevance
“…Figure 3 shows students' mean sense of belonging according to their earned overall letter grade in the course. Students who earned higher grades in each course tend to indicate stronger sense of belonging, similar to the find- ings of Edwards et al [8]. In Year 2 S2, despite the larger proportion of students earning a higher grade (Fig.…”
Section: Sense Of Belonging Relationship With Course Performancesupporting
confidence: 86%
See 1 more Smart Citation
“…Figure 3 shows students' mean sense of belonging according to their earned overall letter grade in the course. Students who earned higher grades in each course tend to indicate stronger sense of belonging, similar to the find- ings of Edwards et al [8]. In Year 2 S2, despite the larger proportion of students earning a higher grade (Fig.…”
Section: Sense Of Belonging Relationship With Course Performancesupporting
confidence: 86%
“…Within large introductory science courses, research hints that students sense of belonging may be tied to various course structures. For examples, Edwards et al found that students' sense of belonging in a general chemistry course may change during a semester according to students' course performance [8]. Kepple and Coble found that students cite both interpersonal relationships with their group and their lab work as significant contributors to their sense of belonging in a physics course [9].…”
Section: Introductionmentioning
confidence: 99%
“…57,58 While much remains to be done 58 to create inclusive learning environments, these trends stress the importance of evaluating curricula and making changes as needed to help students from every background succeed. With this in mind, a strong sense of belonging in STEM is a robust predictor of students' persistence in the field and academic success, 12,13,56,59 particularly for students from groups that are underrepresented. 10 There is tremendous potential value in using course-based laboratory experiences to show students what it is like to work in STEM and develop their transferable skills in a more controlled and low-risk environment early in their scientific careers.…”
Section: Student Outcomes and Discussionmentioning
confidence: 99%
“…Along the same lines, increased science identity among students was even attributed to closing a known “awarding gap” across the United Kingdom higher education system, and other studies in the literature highlight the importance of fostering students’ science identity, especially among HUG students. , While much remains to be done to create inclusive learning environments, these trends stress the importance of evaluating curricula and making changes as needed to help students from every background succeed. With this in mind, a strong sense of belonging in STEM is a robust predictor of students’ persistence in the field and academic success, ,,, particularly for students from groups that are underrepresented . There is tremendous potential value in using course-based laboratory experiences to show students what it is like to work in STEM and develop their transferable skills in a more controlled and low-risk environment early in their scientific careers.…”
Section: Remote Course Designmentioning
confidence: 99%
“…Additionally, although emotional and social engagement were not found to be significantly related to students’ grades on related exam items in this study, these aspects may still be important to students’ learning and should not be overlooked when facilitating active learning in the classroom. For example, some studies have found students’ social relationships, such as sense of belonging, to positively influence students’ overall grade in a course and other studies focused on students’ engagement in STEM courses as a whole found emotional engagement to be positively related to student performance outcomes . Additionally, higher emotional engagement in a course has also been found to be related to higher educational and career aspirations. , …”
Section: Implications For Practicementioning
confidence: 99%